Pregnancy with heart disease: Fetomaternal outcome: A retrospective analysis from a tertiary care teaching hospital in Northern India - Verma, Menka; Ashwani Kumar; Smiti Nanda; Meenakshi Chauhan; Pushpa Dahiya; Savita Rani Singhal (Asian Journal of Medical Sciences, 2023)
Background: Heart diseases are the most significant non-obstetrical causes of maternal deaths, accounting for up to 15% of all cases. The present retrospective analysis is an attempt to assess the spectrum and impact of cardiac diseases on pregnancy. Aims and Objectives: The aims of this study were to analyze the maternal and perinatal outcomes and spectrum of heart disease in pregnancy. Materials and Methods: The study was carried out in the Department of Obstetrics and Gynecology at PGIMS, Rohtak, where retrospective record of inpatient obstetrics registry of pregnant women with cardiac diseases was analyzed. Clinical information obtained from the patient’s medical records including clinical presentation, laboratory investigations, 2-D echocardiography, maternal, and neonatal outcomes were noted. All pregnant women as well as postpartum patient with cardiac disease were included in the study. Results: A total of 62 pregnant women with heart diseases were hospitalized during the study period. Spectrum of heart disease among these women analyzed and we found that the 22 had rheumatic heart disease (RHD), 14 had congenital heart disease (CHD), and 14 had cardiomyopathies (CMP). LSCS was done for 24 and out of these, nine were elective LSCS while 15 were emergency LSCS. Vaginal deliveries were performed in 31 women. Twenty-eight women got shifted to intensive care units during course of treatment. Three intrauterine deaths were noted in our study. Conclusion: We have concluded from the present study and after reviewing the literature about spectrum of heart diseases in pregnancy, that the most common cardiac lesions complicating the pregnancy are RHD followed by CHD and CMP. Successful management of heart disease with pregnancy can be achieved by timely diagnosis and safe transfer of patient to the cardiomaternal tertiary care, where multidisciplinary teams are available.